2017
DOI: 10.1111/pere.12214
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of supportive communication during conversations about coping with relational transgressions

Abstract: Researchers investigating relational transgressions have minimally explored the role of third‐party personal network members in the coping process. It is argued that supportive messages during conversations about coping with relational transgressions are associated with transgressed individuals' perceived stress and feelings about the transgression. Results from a study involving conversations between 50 pairs of personal network members suggest that participants' perceptions of stress and negative emotions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Some studies that might appear on their face to be relationship-related were ultimately excluded from our analysis because we determined they did not meet the criteria described above (i.e., were outside the scope of romantic and sexual relationships). Examples included studies that (a) examined the role of relationship variables as merely a robustness check (e.g., testing for the effect of relationship type as a robustness check; Pederson & Mclaren, 2017); (b) focused on sexual health outcomes, such as condom use or sexually transmitted infection prevention (e.g., a study examining the relationship between alcohol consumption and condom use; MacDonald et al, 1996, Study 1); (c) examined nonconsensual behaviors, such as harassment and sexual coercion (e.g., the association between power and the likelihood of engaging in sexual harassment; Williams et al, 2017, Study 3); (d) examined family relationships without any focused discussion of specific romantic or sexual relationships within the family context (e.g., the disclosure of family secrets to outsiders; Vangelisti & Caughlin, 1997); (e) examined basic physiological responses to sexual stimuli (e.g., a study examining testosterone reactivity in response to erotica; Zilioli et al, 2016); (f) had implications for relationship phenomena but did not include directly relationship-relevant variables (e.g., studies examining attitudes toward same-sex marriage; van der Toorn et al, 2017); or (g) examined relationship-related variables such as attachment without a specific focus on romantic relationships (e.g., Popa-Velea et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies that might appear on their face to be relationship-related were ultimately excluded from our analysis because we determined they did not meet the criteria described above (i.e., were outside the scope of romantic and sexual relationships). Examples included studies that (a) examined the role of relationship variables as merely a robustness check (e.g., testing for the effect of relationship type as a robustness check; Pederson & Mclaren, 2017); (b) focused on sexual health outcomes, such as condom use or sexually transmitted infection prevention (e.g., a study examining the relationship between alcohol consumption and condom use; MacDonald et al, 1996, Study 1); (c) examined nonconsensual behaviors, such as harassment and sexual coercion (e.g., the association between power and the likelihood of engaging in sexual harassment; Williams et al, 2017, Study 3); (d) examined family relationships without any focused discussion of specific romantic or sexual relationships within the family context (e.g., the disclosure of family secrets to outsiders; Vangelisti & Caughlin, 1997); (e) examined basic physiological responses to sexual stimuli (e.g., a study examining testosterone reactivity in response to erotica; Zilioli et al, 2016); (f) had implications for relationship phenomena but did not include directly relationship-relevant variables (e.g., studies examining attitudes toward same-sex marriage; van der Toorn et al, 2017); or (g) examined relationship-related variables such as attachment without a specific focus on romantic relationships (e.g., Popa-Velea et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The mediating role of child‐reported parental support quality also added to a growing body of work that stresses support quality as a mediator between supportive communication and outcomes (e.g., High & Solomon, ; Pederson & McLaren, ). High and Solomon (), for instance, found that evaluations of support quality significantly mediated the associations between person‐centered supportive messages and improvement of stressors three weeks after the supportive communication.…”
Section: Discussionmentioning
confidence: 99%
“…High and Solomon (), for instance, found that evaluations of support quality significantly mediated the associations between person‐centered supportive messages and improvement of stressors three weeks after the supportive communication. Another study focused on conversations about coping with relational transgressions and found evidence for the mediating effects of support quality between the amount of emotional support received and negative emotions related to transgressions (Pederson & McLaren, ). The current findings not only offered additional evidence for the “indirect effect model” (Pederson & McLaren, ) that highlights cognitive evaluations of supportive communication as a vital explanatory factor of social support outcomes, but also demonstrated the applicability of this model to the support gap literature.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that suspected infidelity should follow a similar path. Although some couples who experience infidelity may improve their primary relationship (e.g., Charny & Parnass, 1995; Olson et al, 2002), relational transgressions, such as a partner’s suspected betrayal, can have lingering negative consequences for many (Pederson & McLaren, 2017). Indeed, relationship distress and jealousy are associated with greater depressive symptoms (Riso et al, 2002), health problems (Arnocky et al, 2015), and alcohol and drug use (Buunk & Dijkstra, 2000).…”
Section: Suspected Infidelity and Transactional Stress Theorymentioning
confidence: 99%